Investigating EFL Learners’ Difficulties in Writing Performance. A Case study of Secondary Schools, Gezira State, Sudan,(2020) - Mohamed, Mawaddah Ibrahim Min Alseed (Gezira Journal of Educational Sciences and Humanities; مجلد 20 عدد 2 (2023), 2026)
Writing is one of the most difficult tasks for many of EFL students. This study aims at: investigating EFL learners’ difficulties in writing performance and encouraging EFL teachers to use modern techniques in teaching writing. The study adopted the descriptive analytical method. The data were collected by means of a questionnaire which was distributed to )50( English language teachers at secondary schools in Eastern Gezira Locality, Gezira State (2021).Then the collected data were analyzed by the (SPSS) program. The study came out with many results, the  most important ones are :some EFL  students face problems in writing performance due to the lack of vocabulary, errors in spelling or the use of grammar, most EFL teachers still use traditional method of teaching writing. The study recommends the use of some teaching techniques of developing EFL learners’ writing skills like: extensive reading, collaborative activities, pre-writing  activities, brainstorming techniques and the use of modern technology. الكتابة هي إحدى المهمات التي يصعب علي الكثير من الطلا ب تجويدها . تهدف هذه الدراسة  إلي بحث مشكلات الكتابة التي يعاني منها بعض طلاب اللغة الانجليزية بالمرحلة الثانوية و تشجيع المعلمين علي تدريس مهارة الكتابة باستخدام أساليب تدريس حديثة وفعالة. اتبعت الدراسة المنهج التحليلي الوصفي كما استخدمت الباحثة نظام الاستبانة لجمع البيانات من خمسين (50)   معلماً ومعلمة للغة الإنجليزية  من محلية شرق الجزيرة بولاية  الجزيرة  السودان (2021) . تم تحليل  البيانات بالنظام الإحصائي  ( SPSS)وتوصلت الدراسة الى أن الكثير من طلاب اللغة الانجليزية يرتكبون بعض الأخطاء في واجباتهم الكتابية نتيجة قلة المفردات اللغوية والتهجي أو الضعف في قواعد اللغة .أوصت الدراسة باستخدام بعض أساليب التدريس  الفعالة في تطوير مهارة الكتابة للطلاب مثل القراءة المكثفة والأنشطة التعاونية و أسلوب الأسئلة والانشطة الذهنية واستخدام التقنيات الحديثة.